The analysis of the hashtag #Jokowi404NotFound on Twitter in protesting mural removal in the public sphere - Luky Fitriani; Pawito Pawito; Prahastiwi Utari (Informasi, 2021)
The removal of mural looking like President Joko Widodo's face with the words 404 Not Found triggered a wide range of reactions from the public, including some on Twitter, who saw the action as an anti-critical form of government. As a result, the hashtag #Jokowi404notfound became a popular topic and was used over 11,000 times on August 14, 2021. The purpose of this study is to look at how people use the hashtag #Jokowi404notfound on Twitter to protest the removal of murals. In August 2021, this study takes a qualitative approach, collecting data in the form of observation of media texts on Twitter's public timeline. According to the findings of this study, the hashtag #Jokowi404notfound was used to protest the government's anti-critical decision to remove murals as a form of suppression of individual freedom. When the public interest is at stake and the movement is mobilized by Twitter activists with large social media followings, the hashtag activism movement has the potential to drive and influence government policy. Messages to the government are also conveyed using various styles of language.